Pengaruh Model Pembelajaran Teams Games Tournament Terhadap Hasil Belajar Matematika Siswa Kelas V SD 1 Gribig - Nabila Fakhrin Nihayati; Putri Amelia Noviyanti; Cantika Marlina Marlin; Filyas Aleansyah (Jurnal THEOREMS (The Original Research of Mathematics), 2023)
ABSTRACTEducation in schools has a series of fields of study that must be mastered by students, one of which is mathematics. Learning mathematics prepares students to have a critical mathematical mindset. Learning mathematics about shapes and volumes of objects is considered boring and frightening for some students. To overcome this, the application of the Teams Games Tournament learning model was chosen because it can create a fun and relaxed atmosphere in learning mathematics. This study aims to determine the effect of the Teams Games Tournament learning model on the mathematics learning outcomes of fifth graders at SD 1 Gribig. Research using a quantitative approach to the experimental method. The sampling technique used is non-probability with a sample of 30 fifth grade students at SD 1 Gribig. Data collection was carried out through tests in the form of written tests. Data analysis was performed using SPSS with paired sample t-test. Learning outcomes can be seen from the class average which has increased from 64.3 (pretest) to 76.3 (posttest). The paired t-test shows that the significance value is Î± 0.000 <0.05. This means that Ho is rejected and Ha is accepted. The application of the Teams Games Tournament learning model has an influence on the results of learning mathematics for fifth graders of SD 1 Gribig.Keywords: learning model, TGT, learning achievement.